Corporate social responsibility (CSR) of Malaysian listed property companies / Asma Senawi - Senawi, Asma (2010)
This exploratory research aims to investigate the level of corporate social responsibility (CSR) disclosure among Malaysian Listed Property Companies. In addition, the relationship between the CSR disclosure and several corporate attributes is also examined. To measure the extent of disclosure made by companies, a CSR Disclosure Index was developed specifically for property companies. Content analysis had been used to analyse the activities carried out by companies using annual reports and company websites. Twenty property companies listed on the Main Board of Bursa Malaysia was selected randomly. This study found that very few property companies in Malaysia are making efforts to carry out CSR practices in their businesses. The highest CSR disclosure is community involvement followed by environment, marketplace and workplace. It was also found that significant number of the lowest ranking companies suffered losses during the period under study and significant proportions of the top ranking companies were big size corporations and paid higher audit fees.